Displacement, human rights and sexual and reproductive health : conceptualizing gender protection gaps in Latin America - Cintra, Natalia (Bristol University Press, 2023)
Focusing on the flight of women and girls from Venezuela, this book examines the gendered nature of forced displacement and the ways in which the failures of protection regimes to be sensitive to displacement's gendered character affect women and girls, and their sexual and reproductive health.